Assessment and Management of Posttraumatic Stress Disorder. Issue 3 (June 2018) - Ellis, Janet; Zaretsky, Ari
ABSTRACT: PURPOSE: The goal of this article is to increase clinicians' understanding of posttraumatic stress disorder (PTSD) and improve skills in assessing risk for and diagnosing PTSD. The importance and sequelae of lifetime trauma burden are discussed, with reference to trends in prevention, early intervention, and treatment. RECENT FINDINGS: PTSD has different clinical phenotypes, which are reflected in the changes in Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ( DSM-5 ) criteria. PTSD is almost always complicated by comorbidity. Treatment requires a multimodal approach, usually including medication, different therapeutic techniques, and management of comorbidity. Interest is growing in the neurobiology of childhood survivors of trauma, intergenerational transmission of trauma, and long-term impact of trauma on physical health. Mitigation of the risk of PTSD pretrauma in the military and first responders is gaining momentum, given concerns about the cost and disability associated with PTSD. Interest is also growing in screening for PTSD in medical populations, with evidence of improved clinical outcomes. Preliminary research supports the treatment of PTSD with repetitive transcranial magnetic stimulation. SUMMARY: PTSD is a trauma-related disorder with features of fear and negative thinking about the trauma and the future. Untreated, it leads to ongoing disruption of life due to avoidance, impaired vocational and social functioning, and other symptoms, depending on the phenotype. Despite a theoretical understanding of underlying mechanisms, PTSD remains challenging to treat, although evidence exists for benefit of pharmacologic agents and trauma-focused therapies. A need still remains for treatments that are more effective and efficient, with faster onset.